Pendidikan Perempuan di Pondok Pesantren - Muafiah, Evi (Nadwa, 2013)
This article attempts to show womens education reality in pesantren, par-ticularly pesantren that administers the two institutions at the same time, the education for men and for women. This is certainly different from those car-ry out the education specific for women. Indonesia has started to open edu-cational opportunities for women at the time of R.A. Kartini, in which the previous women education was limited by the culture. The spirit to obtain education that equal with men was stated in her letters. Kartini had inspired some Indonesian women to get education as men. Later, some women who pioneered education for women appeared such as Rahmah el-Yunusiyah, Rangkayo Rasuna Said, Dewi Sartika etc. Each of them established a special school for girls with different studies taught.